EVALUASI PERILAKU SAMBUNGAN BAJA PADA STRUKTUR RANGKA MOMEN TAHAN GEMPA: ANALISIS STUDI LITERATUR DAN STATISTIK TERHADAP SAMBUNGAN TIPE EXTENDED END-PLATE - Oktavianus Chayadi; Edison Hatoguan Manurung; Alip Prajoko (SINERGI : Jurnal Riset Ilmiah, 2026)
Beam–column connections are critical components in seismic-resistant steel moment frame systems. This study aims to evaluate the behavior of Extended End-Plate (EEP) connections through a systematic literature review and statistical analysis of secondary data. The research method adopts a systematic literature review approach with quantitative data analysis derived from five main research journals published between 1997 and 2021. The data were extracted and analyzed using SPSS 25 software through descriptive statistical analysis, Pearson correlation, multiple linear regression, and one-sample t-test. The results indicate that: (1) there is a very strong positive correlation between end-plate thickness and connection moment capacity (r = 0.892; p < 0.01); (2) 67% of connection configurations with end-plate thickness ≥ 15 mm satisfy the minimum inelastic rotation criterion of 0.03 rad based on the FEMA-350 standard; and (3) end-plate thickness contributes dominantly (71.4%) to the increase in moment capacity compared to the number of bolts (28.6%). The recommended optimal configuration is an EEP connection with a 15 mm end-plate thickness and six bolts, producing a moment capacity of 56.8 kNm and an inelastic rotation of 0.042 rad. This study provides practical implications as a basis for recommending EEP connection design for steel buildings in seismic regions of Indonesia